Protective Effect of Stachydrine Against Cerebral Ischemia-Reperfusion Injury by Reducing Inflammation and Apoptosis Through P65 and JAK2/STAT3 Signaling Pathway - Li, Li; Sun, Lili; Qiu, Yan; Zhu, Wenjun; Hu, Kangyuan; Mao, Junqin (Frontiers in Pharmacology, 2020)
Stachydrine, a constituent of Leonurus japonicus Houtt which also called Japanese motherwort has been shown to improve vascular microcirculation and ameliorate endothelial dysfunction. This study investigated the neuroprotective effect of stachydrine. Male Sprague-Dawley (SD) rats were randomly divided into sham, control, and stachydrine groups. The neurological deficit score was evaluated and the infarct size of the brain was measured using 2,3,5-triphenyltetra-zolium (TTC) chloride staining assay, and the pathological changes in the brain tissues were examined by HE staining. Nissl and terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick end labeling (TUNEL) staining were performed to assess the numbers of Nissl bodies and the levels of apoptosis in the neurons. The activities of superoxide dismutase (SOD) and the levels of malondialdehyde (MDA) were also measured. The release of inflammatory factors IL-1β and TNF-α were detected by Enzyme-linked immunosorbent assay (ELISA). Compared with the control group, the stachydrine group showed a significant prevention of neurological deficit, as indicated by the reduced infarct volume in the brain. Moreover, the stachydrine treatment reduced the activities of SOD, the levels of MDA and decreased the amount of IL-1β, and TNF-α, indicating that it could function to decrease the level of inflammation, thus reducing brain damage. The ischemic stroke model of PC12 cells was prepared via oxygen-glucose deprivation (OGD) protocol for 6 h. The expression of P65 and JAK2/STAT3 signaling pathway related proteins was measured by western blot. The treatment group was found to have the survival rate of PC12 cells improved and the release of inflammatory factors reduced when compared with the OGD group. This study demonstrated that stachydrine could improve nerve function by inhibiting the phosphorylation of P65/JAK2 and STAT3.